2005
DOI: 10.1002/jor.20030
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids inhibit tenocyte proliferation and Tendon progenitor cell recruitment

Abstract: Corticosteroid injection is commonly used to treat tendon injuries but is often associated with tendon rupture and impaired tendon healing. The effects of dexamethasone on tenocytes have been studied in vitro but only using high concentrations of dexamethasone in monolayer cultures of tenocytes over short periods of time. We have therefore investigated the effects of physiological and pharmacological concentrations of dexamethasone on monolayer cultures of tenocytes over extended time periods. We have also use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 41 publications
6
77
0
2
Order By: Relevance
“…Moreover, reduced expression of collagen type I mRNA and procollagen type I and II was shown in two studies with tenocytes of chick embryos [35,36]. A concentration-dependent reduction in the number of tenocytes and collagen synthesis was also detected with rat tail tenocytes when exposed over extended time periods [37].…”
Section: Page 14 Of 37mentioning
confidence: 93%
“…Moreover, reduced expression of collagen type I mRNA and procollagen type I and II was shown in two studies with tenocytes of chick embryos [35,36]. A concentration-dependent reduction in the number of tenocytes and collagen synthesis was also detected with rat tail tenocytes when exposed over extended time periods [37].…”
Section: Page 14 Of 37mentioning
confidence: 93%
“…It is important to highlight that the rest and anti-inflammatory are mainly used for the symptomatic relief with no direct effect in the tendinopathy as chronic tendon disorders are predominantly degenerative. Further, both non steroidal antiinflammatory drugs [91] and corticosteroid drugs [92,93] could have deleterious effects on long-term tendon healing.…”
Section: Conservative Treatment Of Shoulder Tendinopathymentioning
confidence: 99%
“…31 Many studies have demonstrated that the administration of corticosteroids in cell cultures from tendons affect tenocyte viability, proliferation, collagen type I synthesis, and migration. 12,13,32,33 In the present study, we used a more similar model to the clinical situation, and instead of administering corticosteroids to cells in culture, we isolated tenocytes from the tendons of animals previously submitted to pharmacological therapy.…”
Section: Discussionmentioning
confidence: 99%